A software reconfigurable optical multiband UWB system utilizing a bit-loading combined with adaptive LDPC code rate scheme - He, Jing; Dai, Min; Chen, Qinghui; Deng, Rui; Xiang, Changqing; Chen, Lin (Optical fiber technology, 2017)
•A bit-loading combined with ALCR algorithm is investigated in MB-OFDM UWBoF system.•A MZM with negative chirp parameter is utilized in MB-OFDM UWB system.•The ALCR algorithm can work effectively in MB-OFDM UWB system.•The SNR is improved by 2.79dB using ALCR when the code rate is 75%.•The Q factor is improved by 3.93dB utilizing bit-loading combined with algorithm. In this paper, an effective bit-loading combined with adaptive LDPC code rate algorithm is proposed and investigated in software reconfigurable multiband UWB over fiber system. To compensate the power fading and chromatic dispersion for the high frequency of multiband OFDM UWB signal transmission over standard single mode fiber (SSMF), a Mach-Zehnder modulator (MZM) with negative chirp parameter is utilized. In addition, the negative power penalty of −1dB for 128QAM multiband OFDM UWB signal are measured at the hard-decision forward error correction (HD-FEC) limitation of 3.8×10−3 after 50km SSMF transmission. The experimental results show that, compared to the fixed coding scheme with the code rate of 75%, the signal-to-noise (SNR) is improved by 2.79dB for 128QAM multiband OFDM UWB system after 100km SSMF transmission using ALCR algorithm. Moreover, by employing bit-loading combined with ALCR algorithm, the bit error rate (BER) performance of system can be further promoted effectively. The simulation results present that, at the HD-FEC limitation, the value of Q factor is improved by 3.93dB at the SNR of 19.5dB over 100km SSMF transmission, compared to the fixed modulation with uncoded scheme at the same spectrum efficiency (SE).